Penerapan Analisis Biomassa Shoot-Root Ratio dalam Memprediksi Hasil pada Genotipe Ercis - Amrul Mubarok; Annisa Nur; Budi Waluyo (Paspalum: Jurnal Ilmiah Pertanian, 2024)
The economic and nutritional potential of peas makes them highly promising for development. Accurate yield predictions based on photosynthate allocation are essential for optimizing crop production. This study aimed to utilize shoot-root ratio biomass analysis to predict the yield of different pea genotypes. The research was conducted at the experimental field of the Faculty of Agriculture, University of Brawijaya, located in Jatimulyo, Malang, East Java. The study utilized three pea genotypes (TMG-8-2, BTG-1, and BW-44181-3-1) planted in individual rows. The analysis involved calculating the shoot-root ratio and using simple linear regression to predict the results. The findings indicated that the shoot-root ratio varied over time, with the BW-44181-3-1 genotype displaying the highest ratio and the TMG-8-2 genotype showing the lowest. The shoot-root ratio exhibited the highest increase during the generative phase, peaking during pod maturation. Regarding yield variables, the results of the simple linear regression analysis revealed that the shoot-root ratio significantly influenced the number of pods planted (R2 = 88%), the number of seeds planted (R2 = 78%), and the weight of seeds planted (R2 = 90%) at 70 days after planting (DAP). An increase in the shoot-root ratio served as an indicator of the quantity and weight of seeds planted, as well as the number of pods produced.